Micron-sized polymer microspheres and preparation method and application thereof
By adopting polymer microspheres with specific ratios, the problem of insufficient heat resistance performance of lithium-ion battery separators during high-strength operation is solved, and the heat resistance and flame retardant performance of micron-level polymer microspheres are improved, and the battery separators are improved security.
Patent Information
- Application Number
- CN202411405717.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The internal temperature of lithium-ion batteries rises sharply during high-intensity operation, which may lead to fire and insufficient flame retardant and heat resistance of existing battery separators.
Micron-scale polymer microspheres prepared by using styrene, norbornene modified silica, methyl acrylate and hydroxyethyl methacrylate as raw materials. The microspheres have a core-shell structure and the core layer is modified from two The shell is composed of silicon oxide, and the shell contains a phosphoric acid structure, which regulates the high temperature resistance and flame retardant properties of the microspheres through specific ratios.
It has achieved good heat resistance and mechanical properties of micron-scale polymer microspheres, can withstand high temperature shrinkage and uniform size, improves the flame retardant and heat resistance of the battery separator, and reduces fire risk.
Smart Images

Figure CN118909207B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer functional materials, and in particular to micron-sized polymer microspheres and a preparation method and application thereof. Background Art
[0002] Polymer microspheres refer to spherical polymer particles with diameters ranging from micrometers to nanometers. They can be made of natural or synthetic polymer materials. According to their structure and function, polymer microspheres can be divided into solid, hollow, composite microspheres and porous polymer microspheres. Solid microspheres are solid polymer spheres with a three-dimensional cross-linked network structure; hollow microspheres are shell structures and can be divided into single-shell, double-shell and multi-shell structures. They have a high specific surface area and are suitable for thermal insulation materials. They are also widely used in catalysis, medicine, environment, adsorbents and other fields; composite microspheres are the most common core-shell structure microspheres, which have a core inside and a shell covering the outside. They are widely used in the battery field; porous polymer microspheres have a high specific surface area due to the presence of a porous structure, and are easy to process and have good filling properties. They are widely used in catalysis, sensing, electronics, adsorption and separation and other fields.
[0003] However, conventional polymer microspheres have problems such as uneven size. To address this problem, CN112791674B discloses "a core-shell type micron-sized monodisperse silica microsphere and its preparation method". Carboxylated polystyrene microspheres are prepared using polystyrene microsphere dispersion and acrylic monomers as main raw materials. The prepared carboxylated polystyrene microspheres are modified by using tetraoxyethylsilane hydrolyzate to obtain micron-sized monodisperse silica microspheres with high uniformity. Another example is CN109786749A discloses "a cross-linked SBR microsphere binder and preparation method and lithium-ion battery containing the binder". The pre-treated butadiene and styrene are blended and polymerized with other additives such as modified monomers and porogenic agents to obtain an SBR microsphere binder. The SBR microsphere binder has a porous cross-linked structure with a particle size range of 10nm~1μm.
[0004] In lithium-ion batteries, the function of the diaphragm is to isolate the positive and negative electrodes to prevent internal short circuits. The performance of the diaphragm has an important impact on the safety, capacity, cycle life and power density of the battery. In order to improve the performance of the diaphragm, polymer microspheres, as a new type of diaphragm modification material, have shown great potential and advantages in the binder of battery diaphragms. For example, CN112531290B discloses "a ceramic microsphere, a diaphragm containing the ceramic microsphere and a lithium-ion battery containing the diaphragm". Conductive microspheres and ceramic microspheres are prepared by a polymer coating method, which can improve the safety performance of lithium-ion batteries.
[0005] However, when lithium batteries work at high intensity, their internal temperature rises sharply and may even cause fires, which places higher requirements on the flame retardancy and heat resistance of battery separators.
[0006] Therefore, it is urgent to develop a binder for battery separators that has heat resistance, good mechanical properties, and polymer microspheres that can withstand high temperature shrinkage. Summary of the invention
[0007] The main purpose of the present invention is to provide a micron-sized polymer microsphere and a preparation method thereof. The micron-sized polymer microsphere has good heat resistance and mechanical properties, can resist high temperature shrinkage, and has uniform and stable size.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] In one aspect, the present invention provides a method for preparing micron-sized polymer microspheres, comprising the following steps:
[0010] S1, mixing the mixed monomer A and the dispersant with an ethanol solution to prepare a monomer mixed solution;
[0011] S2. In an inert gas atmosphere, the initiator and the monomer mixture in step S1 are mixed and emulsified, and the mixture is heated to 60-70° C. and stirred at a constant temperature for 1-2 hours to obtain a core layer emulsion;
[0012] S3, mixing and dispersing the mixed monomer B and the emulsifier to obtain a shell emulsion;
[0013] S4, dropwise adding the shell emulsion in step S3 to the core emulsion in step S2, adding an initiator, continuing constant temperature stirring for 23 to 26 hours, washing after the reaction is completed, and obtaining micron-sized polymer microspheres;
[0014] The mixed monomer A comprises styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate;
[0015] The mixed monomer B includes 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride.
[0016] The micron-sized polymer microspheres of the present application are uniform and stable in size. At the same time, the core layer has a high-hardness modified silica that can prevent shrinkage at high temperatures. The phosphate structure of the outer shell layer can improve the flame retardant properties of the polymer microspheres. The phenyl groups therein can form a π-π stacking effect to improve the high-temperature resistance of the polymer microspheres. In addition, they can interact with the phenyl groups in the core layer to make the polymer microsphere structure more stable and have higher mechanical properties.
[0017] In some embodiments, the mass ratio of styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate is 1:(0.2-0.4):(0.7-0.9):(0.08-0.1).
[0018] Preferably, the mass ratio of styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate is 1:0.3:0.8:0.09.
[0019] The present application adjusts the mass ratio of styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate. On the one hand, the rigid structure of styrene and norbornene-modified silica can make the structure of the microsphere more stable. In addition, the norbornene structure in the norbornene-modified silica enhances the high temperature resistance of the core layer of the polymer microsphere. On the other hand, the expansion performance of the polymer microsphere can be reduced by adjusting the specific ratio.
[0020] The present application does not make any special limitation on the dispersant, which is a commonly used dispersant by those skilled in the art, including but not limited to polyvinyl pyrrolidone.
[0021] In some embodiments, the mass of the dispersant is 0.1 to 0.2 times the mass of the mixed monomer A.
[0022] The present application does not specifically limit the initiator, which is a commonly used initiator by those skilled in the art, including but not limited to azobisisobutyronitrile.
[0023] In some embodiments, in step S2, the mass of the initiator is 0.01-0.02 of the mass of the mixed monomer A.
[0024] In some embodiments, in step S4, the mass of the initiator is 0.01 to 0.02 times the total mass of the mixed monomer A and the mixed monomer B.
[0025] In some embodiments, the method for preparing the norbornene-modified silica comprises the following steps:
[0026] A1. Mix silica and thionyl chloride, add N,N-dimethylformamide, heat to 40-50°C and stir for 3-5h, cool to room temperature, quench, concentrate and dry under reduced pressure to obtain acyl chloride silica;
[0027] A2. Under an inert gas atmosphere, 4-hydroxy-2-butanone and the acyl chloride silicon dioxide in step A1 are mixed, added with acetone for dispersion, an acid binding agent is added, the temperature is raised to 40-60° C. and stirred at a constant temperature for 12-14 hours. After the reaction is completed, the mixture is filtered, concentrated and dried under reduced pressure to obtain keto-modified silicon dioxide;
[0028] A3. Mix the keto-modified silica in step A2 with 5-norbornene-2-methylamine, add methanol, add an acid binding agent, heat to 60-70° C. and stir at a constant temperature for 6-8 hours. After the reaction is completed, filter to obtain norbornene-modified silica.
[0029] Silicon dioxide itself has good high temperature resistance and wear resistance, but its compatibility with polymers is poor, which affects the performance of the core layer, making the strength of the core layer uneven and possibly causing local shrinkage and collapse due to heat.
[0030] The present application modifies silica so that its surface can be given a double bond structure. During the preparation of the core layer, it can undergo a cross-linking reaction with other monomers to form an emulsion-coated microsphere seed, which not only enables silica to be grafted into the core layer polymer structure, but also can further enhance the strength and high temperature resistance of the core layer.
[0031] In some embodiments, the molar ratio of 4-hydroxy-2-butanone in step A2 to 5-norbornene-2-methylamine in step A3 is 1:(0.3-0.5).
[0032] Preferably, the molar ratio of 4-hydroxy-2-butanone in step A2 to 5-norbornene-2-methylamine in step A3 is 1:0.4.
[0033] The present application controls the double bond structure therein to reduce the crosslinking density of the core layer by regulating the molar ratio of 4-hydroxy-2-butanone to 5-norbornene-2-methylamine, thereby preventing the increase in crosslinking density from increasing the particle size of the microspheres, which is not conducive to their application in the adhesive of the diaphragm. A larger particle size of the microspheres may reduce the porosity of the adhesive layer, resulting in reduced battery charge and discharge efficiency. In addition, the excess ketone groups therein can also form hydrogen bonds with the shell layer, making the shell layer and the core layer more tightly coated, thereby preventing thermal shrinkage from causing a larger deformation of the polymer microspheres and affecting the performance of the diaphragm.
[0034] In some embodiments, in step A2, the mass ratio of 4-hydroxy-2-butanone to silicon dioxide chloride is (0.4-0.5):1.
[0035] Preferably, in step A2, the mass ratio of 4-hydroxy-2-butanone to silicon dioxide chloride is 0.45:1.
[0036] In some embodiments, the mass ratio of 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride is 1:(0.3-0.5):(0.1-0.2):(0.3-0.5).
[0037] Preferably, the mass ratio of 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride is 1:0.4:0.15:0.4.
[0038] The present application can prevent the increase in crosslinking density from leading to an increase in the hydrophobicity of the microspheres, which is not conducive to the migration of ions in the electrolyte, by regulating the mass ratio of 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride.
[0039] In some embodiments, the acid binding agent is triethylamine.
[0040] The present application does not specifically limit the emulsifier, which is an emulsifier commonly used by those skilled in the art, including but not limited to sodium dodecyl sulfate.
[0041] In some embodiments, the mass of the emulsifier is 0.01 to 0.03 times the mass of the mixed monomer B.
[0042] In some embodiments, the mass ratio of the mixed monomer A to the mixed monomer B is 1:(2-4).
[0043] In some embodiments, the preparation method of the modified maleic anhydride comprises the following steps: mixing maleic anhydride with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 1-naphthylethanol, adding chloroform to disperse, then heating to 55-60°C and stirring at a constant temperature for 8-10 hours. After the reaction is completed, column chromatography is performed to obtain modified maleic anhydride, whose structural formula is shown in Formula I
[0044] (I).
[0045] The modified maleic anhydride of the present application can form a shell layer of microspheres with 2-hydroxyethyl acrylate, carboxyethyl acrylate, and ethylene glycol dimethacrylate. The phosphate groups therein can improve the flame retardant properties of the microspheres and prevent the battery from overheating during high-load operation and causing fires. In addition, the phenyl groups therein can form π-π stacking to improve the high-temperature stability of the microspheres.
[0046] In some embodiments, the molar ratio of maleic anhydride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 1-naphthylethanol is 1:(0.9~1):(0.9~1).
[0047] Preferably, the molar ratio of maleic anhydride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 1-naphthylethanol is 1:0.95:0.95.
[0048] Another aspect of the present invention provides micron-sized polymer microspheres prepared by the above technical solution.
[0049] In another aspect, the present invention provides a use of micron-sized polymer microspheres in a binder for battery separators.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The present invention first uses styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate as raw materials to prepare a microsphere emulsion, and then uses 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride to prepare a shell layer to coat the microsphere emulsion, thereby forming a core-shell structured polymer microsphere. The polymer microsphere is used as a binder for battery separators, has good heat resistance and mechanical properties, can withstand high temperature shrinkage, and has uniform and stable dimensions.
[0052] (2) The norbornene-modified silica of the present invention can impart a double bond structure to its surface. During the preparation of the core layer, it can undergo a cross-linking reaction with other monomers to form an emulsion-coated microsphere seed, which not only enables the silica to be grafted into the core layer polymer structure, but also can further enhance the strength and high temperature resistance of the core layer.
[0053] (3) The modified maleic anhydride of the present invention has phenyl groups that can form π-π stacking to improve the high temperature stability of the microspheres. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a particle size distribution diagram of the micron-sized polymer microspheres prepared in Example 1 of the present application.
[0055] Figure 2 This is a particle size distribution diagram of the micron-sized polymer microspheres prepared in Example 4 of the present application.
[0056] Figure 3 This is a particle size distribution diagram of the micron-sized polymer microspheres prepared in Example 8 of the present application.
[0057] Figure 4 This is the particle size distribution diagram of the micron-sized polymer microspheres prepared in Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0058] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] In the following preparation examples, embodiments and comparative examples, silicon dioxide was purchased from Nanjing Xinhuayuan Chemical Co., Ltd.; polyvinyl pyrrolidone was purchased from Jinan Yuyi Chemical Co., Ltd.
[0060] Preparation Example 1
[0061] A method for preparing norbornene-modified silicon dioxide comprises the following steps:
[0062] A1. Mix 10 g of silica with 100 mL of thionyl chloride, add 0.5 mL of N,N-dimethylformamide, heat to 45 °C and stir for 4 h, cool to 27 °C, quench, and concentrate and dry under reduced pressure to obtain acyl chloride silica;
[0063] A2. Under N2 atmosphere, 5 g (56 mmol) of 4-hydroxy-2-butanone and 11 g of the acyl chloride silica prepared in step A1 were mixed and dispersed in 200 mL of acetone, and 72 mmol of triethylamine was added. The mixture was heated to 50° C. and stirred at constant temperature for 13 h. After the reaction was completed, the mixture was filtered, concentrated under reduced pressure, and dried to obtain keto-modified silica.
[0064] A3. Mix the keto-modified silica in step A2 with 2.7 g (22 mmol) of 5-norbornene-2-methylamine, add 50 mL of methanol, add 29 mmol of triethylamine, raise the temperature to 65° C. and stir at this temperature for 7 h. After the reaction is completed, filter to obtain norbornene-modified silica.
[0065] Preparation Example 2
[0066] The preparation method of norbornene-modified silica is the same as that of Preparation Example 1, except that the amount of 5-norbornene-2-methylamine is 56 mmol.
[0067] Preparation Example 3
[0068] The preparation method of cyclohexane-modified silica is the same as that of Preparation Example 1, except that an equal mole of cyclohexylmethylamine is used instead of 5-norbornene-2-methylamine.
[0069] Preparation Example 4
[0070] The preparation method of methylene-modified silica is the same as that of Preparation Example 1, except that an equal mole of 2-methylallylamine is used instead of 5-norbornene-2-methylamine.
[0071] Preparation Example 5
[0072] The preparation method of modified maleic anhydride comprises the following steps: 80 mmol of maleic anhydride is mixed with 96 mmol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 76 mmol of 1-naphthylethanol, 100 mL of chloroform is added for dispersion, and then the mixture is heated to 57° C. and stirred at a constant temperature for 9 hours. After the reaction is completed, the modified maleic anhydride is obtained by column chromatography, and the structural formula thereof is shown in Formula I.
[0073] (I).
[0074] Preparation Example 6
[0075] The preparation method of modified maleic anhydride is the same as that of Preparation Example 5, except that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide is not added.
[0076] Preparation Example 7
[0077] The preparation method of modified maleic anhydride is the same as that of Preparation Example 5, except that 1-naphthylethanol is not added.
[0078] Example 1
[0079] A method for preparing micron-sized polymer microspheres comprises the following steps:
[0080] S1, mixing 10 g of mixed monomer A and 1.5 g of polyvinyl pyrrolidone with 150 mL of ethanol solution to prepare a monomer mixture;
[0081] S2. Under N2 atmosphere, 0.15 g of azobisisobutyronitrile and the monomer mixture in step S1 were mixed and emulsified, and the mixture was heated to 65° C. and stirred at the constant temperature for 1.5 h to obtain a core layer emulsion;
[0082] S3, 30g of mixed monomer B and 0.6g of sodium dodecyl sulfate were mixed and dispersed to obtain a shell emulsion;
[0083] S4, dropwise adding the shell layer emulsion in step S3 to the core layer emulsion in step S2, and adding 0.6 g of sodium persulfate, and continuing stirring at 65° C. for 24 h. After the reaction is completed, washing is performed to obtain micron-sized polymer microspheres;
[0084] Wherein, the mixed monomer A comprises styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate in a mass ratio of 1:0.3:0.8:0.09; the mixed monomer B comprises 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride in a mass ratio of 1:0.4:0.15:0.4; the norbornene-modified silica is prepared by Preparation Example 1, and the modified maleic anhydride is prepared by Preparation Example 5. The average particle size is 2.5629 μm.
[0085] Example 2
[0086] A method for preparing micron-sized polymer microspheres comprises the following steps:
[0087] S1, mixing 10 g of mixed monomer A and 1 g of polyvinyl pyrrolidone with 150 mL of ethanol solution to prepare a monomer mixture;
[0088] S2. Under N2 atmosphere, 0.1 g of azobisisobutyronitrile and the monomer mixture in step S1 were mixed and emulsified, and the mixture was heated to 60° C. and stirred at constant temperature for 2 h to obtain a core layer emulsion;
[0089] S3, 30g of mixed monomer B and 0.3g of sodium dodecyl sulfate were mixed and dispersed to obtain a shell emulsion;
[0090] S4, dropwise adding the shell layer emulsion in step S3 to the core layer emulsion in step S2, and adding 0.4 g of sodium persulfate, and continuing stirring at 60° C. for 26 h. After the reaction is completed, washing is performed to obtain micron-sized polymer microspheres;
[0091] Wherein, the mixed monomer A comprises styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate in a mass ratio of 1:0.2:0.7:0.08; the mixed monomer B comprises 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride in a mass ratio of 1:0.3:0.1:0.3; the norbornene-modified silica is prepared by Preparation Example 1, and the modified maleic anhydride is prepared by Preparation Example 5. The average particle size is 2.4853 μm.
[0092] Example 3
[0093] A method for preparing micron-sized polymer microspheres comprises the following steps:
[0094] S1, mixing 10 g of mixed monomer A and 2 g of polyvinyl pyrrolidone with 150 mL of ethanol solution to prepare a monomer mixture;
[0095] S2, under N2 atmosphere, 0.2 g of azobisisobutyronitrile and the monomer mixture in step S1 were mixed and emulsified, and the mixture was heated to 70° C. and stirred at constant temperature for 1 h to obtain a core layer emulsion;
[0096] S3, 30g of mixed monomer B and 0.9g of sodium dodecyl sulfate were mixed and dispersed to obtain a shell emulsion;
[0097] S4, dropwise adding the shell layer emulsion in step S3 to the core layer emulsion in step S2, and adding 0.8 g of sodium persulfate, and continuing stirring at 70° C. for 23 h. After the reaction is completed, washing is performed to obtain micron-sized polymer microspheres;
[0098] Wherein, the mixed monomer A comprises styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate in a mass ratio of 1:0.4:0.9:0.1; the mixed monomer B comprises 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride in a mass ratio of 1:0.5:0.2:0.5; the norbornene-modified silica is prepared by Preparation Example 1, and the modified maleic anhydride is prepared by Preparation Example 5. The average particle size is 2.5981 μm.
[0099] Example 4
[0100] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as Example 1, except that the norbornene-modified silica is prepared by Preparation Example 2. The average particle size is 3.8514 μm.
[0101] Example 5
[0102] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as Example 1, except that the modified maleic anhydride is prepared by Preparation Example 6. The average particle size is 2.2685 μm.
[0103] Example 6
[0104] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as Example 1, except that the modified maleic anhydride is prepared by Preparation Example 7. The average particle size is 2.6251 μm.
[0105] Example 7
[0106] A method for preparing micron-sized polymer microspheres, the specific implementation manner is the same as that of Example 1, except that the mixed monomer A comprises styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate in a mass ratio of 1:0.3:1.3:0.09.
[0107] Example 8
[0108] A method for preparing micron-sized polymer microspheres, the specific implementation manner is the same as that of Example 1, except that the amount of sodium persulfate added in step S4 is 1.4 g.
[0109] Comparative Example 1
[0110] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as Example 1, except that an equal mass of cyclohexane-modified silica is used instead of norbornene-modified silica, and the cyclohexane-modified silica is prepared by Preparation Example 3.
[0111] Comparative Example 2
[0112] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as Example 1, except that an equal mass of methylene-modified silica is used instead of norbornene-modified silica, and the methylene-modified silica is prepared by Preparation Example 4.
[0113] Comparative Example 3
[0114] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as that of Example 1, except that an equal mass of silicon dioxide is used instead of norbornene-modified silicon dioxide.
[0115] Comparative Example 4
[0116] A method for preparing micron-sized polymer microspheres, the specific implementation method is the same as that of Example 1, except that an equal mass of maleic anhydride is used instead of modified maleic anhydride.
[0117] Performance Testing:
[0118] (1) Particle size test: Mastersizer 2000 laser particle size analyzer was used to detect the median particle size and particle size distribution of micron-sized polymer microspheres;
[0119] (2) Heat resistance test: Place the polymer microspheres in a 150°C environment for 3 hours, take them out and retest the particle size, and calculate the thermal shrinkage rate according to the following formula:
[0120] Thermal shrinkage rate (%) = (M1-M2) / M1×100%;
[0121] Wherein, M1 is the initial median particle size of the polymer microspheres, and M2 is the median particle size of the polymer microspheres after heat shrinkage;
[0122] (3) Swelling test: The micron-sized polymer microspheres were immersed in electrolyte for 3 days and then the particle size was tested. The swelling rate was calculated according to the following formula:
[0123] Swelling rate (%) = (D2-D1) / D1×100%;
[0124] Wherein, D1 is the initial median particle size of the polymer microspheres, and D2 is the median particle size of the polymer microspheres after expansion;
[0125] (4) Hardness test: 10 parts by weight of polyurethane acrylate (purchased from Yinhuang Industrial Co., Ltd.), 10 parts by weight of TPGDA, 0.2 parts by weight of photoinitiator 1173 and 1 part by weight of polymer microspheres were mixed and applied to the surface of the aluminum plate. The pencil hardness of the cured film was measured manually using a BYK trolley pencil hardness tester according to GB / T6739-1996 and ASTMD3363-00.
[0126] (5) Flame retardant grade: The flame retardant properties of the cured film are graded according to the test method (4) of GB / T 2408-2021 "Test methods for combustion performance of plastics - horizontal and vertical methods".
[0127] The high molecular weight copolymer dispersants of the embodiments and comparative examples were tested according to the above test method. The results are shown in Table 1.
[0128] Table 1
[0129]
[0130] According to the above results, it is found that the polymer microspheres of Examples 1 to 3 have good heat resistance and flame retardant properties, good mechanical properties, can withstand high temperature shrinkage, and have uniform and stable size; Example 4 changes the molar ratio of 4-hydroxy-2-butanone to 5-norbornene-2-methylamine, so that the crosslinking density of the polymer microspheres is increased, the particle size and hardness are increased, and the swelling performance is reduced, but the distribution range of the particle size is wide; Example 5 does not add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide, resulting in a decrease in the flame retardant properties of the polymer microspheres; Example 6 does not add 1-naphthylethanol, resulting in a slight decrease in the heat resistance of the polymer microspheres; Example 7 changes the mass ratio of styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate, resulting in the polymer The swelling property of the polymer microspheres is improved; in Example 8, the crosslinking density of the polymer microspheres is increased, the particle size is increased, and the particle size distribution is widened due to the change in the ratio of sodium persulfate to the total mass of the mixed monomer A and the mixed monomer B; in Comparative Example 1, cyclohexane-modified silica is used instead of norbornene-modified silica, resulting in a decrease in the particle size of the polymer microspheres and a decrease in hardness; in Comparative Example 2, methylene-modified silica is used instead of norbornene-modified silica, resulting in a decrease in the heat resistance of the polymer microspheres; in Comparative Example 3, the hardness of the polymer microspheres is reduced, the particle size is small, and the size distribution is uneven due to the use of the same mass of silica instead of norbornene-modified silica; in Comparative Example 4, maleic anhydride is used instead of modified maleic anhydride, resulting in a decrease in the flame retardancy and heat resistance of the polymer microspheres.
[0131] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing micron-sized polymer microspheres, characterized in that: The steps include: S1, mixing the mixed monomer A and the dispersant with an ethanol solution to prepare a monomer mixed solution; S2. In an inert gas atmosphere, the initiator and the monomer mixture in step S1 are mixed and emulsified, and the mixture is heated to 60-70° C. and stirred at a constant temperature for 1-2 hours to obtain a core layer emulsion; S3, mixing and dispersing the mixed monomer B and the emulsifier to obtain a shell emulsion; S4, dropwise adding the shell emulsion in step S3 to the core emulsion in step S2, adding an initiator, continuing constant temperature stirring for 23 to 26 hours, washing after the reaction is completed, and obtaining micron-sized polymer microspheres; The mixed monomer A includes styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate; The mixed monomer B includes 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride; The method for preparing the norbornene-modified silica comprises the following steps: A1. Mix silica and thionyl chloride, add N,N-dimethylformamide, heat to 40-50°C and stir for 3-5 hours, cool to room temperature, quench, and concentrate and dry under reduced pressure to obtain chlorided silica; A2. Under an inert gas atmosphere, 4-hydroxy-2-butanone and the silicon dioxide chloride in step A1 are mixed, added with acetone for dispersion, an acid binding agent is added, the temperature is raised to 40-60° C. and stirred at a constant temperature for 12-14 hours. After the reaction is completed, the mixture is filtered, concentrated and dried under reduced pressure to obtain keto-modified silicon dioxide; A3, the keto-modified silica in step A2 is mixed with 5-norbornene-2-methylamine, methanol is added, an acid binding agent is added, the temperature is raised to 60-70° C. and stirred at a constant temperature for 6-8 hours, and after the reaction is completed, the mixture is filtered to obtain norbornene-modified silica; The preparation method of modified maleic anhydride comprises the following steps: mixing maleic anhydride with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 1-naphthylethanol, adding chloroform for dispersion, then heating to 55-60°C and stirring at a constant temperature for 8-10 hours, and after the reaction is completed, column chromatography is performed to obtain modified maleic anhydride, the structural formula of which is shown in Formula I (Ⅰ)。 2. The method for preparing micron-sized polymer microspheres according to claim 1, characterized in that: The mass ratio of styrene, norbornene-modified silica, methyl acrylate and hydroxyethyl methacrylate is 1:(0.2-0.4):(0.7-0.9):(0.08-0.1).
3. The method for preparing micron-sized polymer microspheres according to claim 1, characterized in that: The molar ratio of 4-hydroxy-2-butanone in step A2 to 5-norbornene-2-methylamine in step A3 is 1:(0.3-0.5).
4. The method for preparing micron-sized polymer microspheres according to claim 1, characterized in that: The mass ratio of the 2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate and modified maleic anhydride is 1:(0.3-0.5):(0.1-0.2):(0.3-0.5).
5. The method for preparing micron-sized polymer microspheres according to claim 1, characterized in that: In step S4, the mass of the initiator is 0.01 to 0.02 times the total mass of the mixed monomer A and the mixed monomer B.
6. The method for preparing micron-sized polymer microspheres according to claim 1, characterized in that: The molar ratio of maleic anhydride, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-ethanol 10-oxide and 1-naphthylethanol is 1:(0.9-1):(0.9-1).
7. A micron-sized polymer microsphere obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the micron-sized polymer microspheres according to claim 7 in a binder for battery separators.
Citation Information
Patent Citations
Cross-linked SBR microsphere adhesive, preparation method and lithium ion battery containing adhesive
CN109786749A
A ceramic microsphere, a separator containing the ceramic microsphere, and a lithium-ion battery containing the separator.
CN112531290B
Hollow nano silica microsphere modified polyacrylate nuclear shell structure composite emulsion and thin film
CN101899128A
Aqueous binder for lithium ion battery as well as preparation method and application thereof
CN105131875A
Cited By
Controllable thermal expansion microsphere based on bio-based copolymer and preparation method thereof
CN121108570A
Controllable thermal expansion microspheres based on bio-based copolymer and method for preparing the same
CN121108570B